2018
DOI: 10.1139/apnm-2017-0813
|View full text |Cite
|
Sign up to set email alerts
|

Acute dietary nitrate supplementation does not attenuate oxidative stress or the hemodynamic response during submaximal exercise in hypobaric hypoxia

Abstract: The purpose of this study was to investigate changes in oxidative stress, arterial oxygen saturation (SaO), blood pressure (BP), and heart rate (HR) during exercise in hypobaric hypoxia following acute dietary nitrate supplementation. Nine well-trained (maximal oxygen consumption, 60.8 ± 7.8 mL·kg·min) males (age, 29 ± 7 years) visited the laboratory on 3 occasions, each separated by 1 week. Visit 1 included a maximal aerobic cycling test and five 5-min increasing-intensity exercise bouts in a normobaric envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 62 publications
1
21
1
Order By: Relevance
“…In addition, in the acute group, the nitrate supplementation did not attenuate oxidative stress. These results corroborate an earlier study, which showed that acute dietary nitrate supplementation did not attenuate oxidative stress [18]. Therefore, chronic nitrate supplementation can be an alternative method for improving oxidative stress after physical exercise.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, in the acute group, the nitrate supplementation did not attenuate oxidative stress. These results corroborate an earlier study, which showed that acute dietary nitrate supplementation did not attenuate oxidative stress [18]. Therefore, chronic nitrate supplementation can be an alternative method for improving oxidative stress after physical exercise.…”
Section: Discussionsupporting
confidence: 91%
“…Likewise, there is little evidence on the influence of nitrate supplementation on oxidative stress in physical exercise. Carriker et al [18] showed that acute dietary nitrate supplementation does not attenuate oxidative stress during submaximal exercise. However, no study showed the effect of chronic nitrate supplementation on oxidative stress after exercise.…”
Section: Introductionmentioning
confidence: 99%
“…The sample calculation was performed using G.Power 3.1, using as main variable the variation of catalase after BJ ingestion and exercise (−33:18 ± 35 nmol/min/mL) [30]. Therefore, we found that the minimum sample should be 12 (power of 0.80; effect size of 0.474; alpha of 0.05; 3 groups and 4 measures).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, several studies have found that BRJ improves exercise tolerance or rate of perceived exhaustion in normoxia (Aucouturier et al 2015;Bailey et al 2015;Balsalobre-Fern andez et al 2018;Breese et al 2013;Wylie, Kelly, Fulford, et al 2013) as well as hypoxia (Kelly et al 2014;Vanhatalo et al 2011). Other studies, however, have failed to show such an effect on oxidative stress (Carriker et al 2018), rate of fatigue or perceived exertion (de Castro, de Assis Manoel, et al 2019;Lee et al 2019).…”
Section: General Effects Of Brj On Skeletal Muscles and Oxygen Consummentioning
confidence: 99%